Pemberdayaan Masyarakat dalam Pengelolaan Sampah dari Limbah Sayuran di Kwt Kenanga, Kelurahan Kedung Waringin Kecamatan Bojong Gede, Kabupaten Bogor - Srikandi Srikandi; Nia Sonani; Feni Marnilin; Dewi Fitrianti; Mulyana Gustira Putra (Jurnal Abdimas Adpi Sosial dan Humaniora, 2023)
Organic Fertilizers are fertilizers made from various natural ingredients. These natural ingredients can come from leaf litter or from food waste and leftovers. Garbage and food waste is fermented anaerobically (without oxygen) and without the help of the sun. The purpose of this activity is to introduce the manufacture of organic fertilizer from vegetable waste to the Kedung Waringin Village community. The material provided in this activity is how to utilize vegetable waste into products that have economic value. The material includes processing waste into organic fertilizer. The material is given by way of presentation using PowerPoint. The method of this activity is in the form of counseling and training to provide insight into organic fertilizers. The results of the socialization of organic fertilizers showed that the knowledge of the ylang-ylang women farming group increased by an average of 7% through the pretest and post-test values ​​during the socialization. Based on the evaluation, it shows that the women farmer group has been able to make organic fertilizer independently. Socialization on the manufacture of organic fertilizers provides additional insight for women farmer groups on the use of organic fertilizers for agriculture.